2022
DOI: 10.1159/000525624
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal versus Port-Site Specimen Retrieval after Laparoscopic Myomectomy: A Systematic Review and Meta-Analysis

Abstract: Introduction: To date, there is no robust evidence suggesting whether transvaginal (TVSR) or port-site specimen retrieval (PSSR) after laparoscopic myomectomy (LM) may lead to better surgical outcomes. Considering this element, we aimed to compare surgical outcomes of TVSR versus PSSR after LM. Methods: A search (PROSPERO ID: CRD42020176490) of international databases, from 1980 to 2020, in English language, was conducted. We selected studies that included women who underwent LM with TVSR compared with PSSR. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Although different types of specimen retrieval are available, including transvaginal extraction, and have several advantages, such as less pain postoperatively 25,26 . In the present study, all specimens were in‐bag and removed through the umbilical incision.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although different types of specimen retrieval are available, including transvaginal extraction, and have several advantages, such as less pain postoperatively 25,26 . In the present study, all specimens were in‐bag and removed through the umbilical incision.…”
Section: Discussionmentioning
confidence: 97%
“…as less pain postoperatively. 25,26 In the present study, all specimens were in-bag and removed through the umbilical incision. As the incision is relatively large and the teratoma tissue is soft (except the nodule), there is no need to add an additional incision, thus reducing the chance of infection and injury.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mean hospital stay was shorter for the LM group than for the AM group, corroborating the reports of previous studies ( 13 , 24 , 25 ), thereby confirming the major advantage of the laparoscopic approach. Furthermore, a recent meta-analysis ( 26 ) which compared transvaginal retrieval and port-site specimen retrieval after LM showed comparable results in terms of intraoperative complications, hospital stay and operative time. Concerning transvaginal extraction of the surgical specimen after LM, a large case series by Laganá et al ( 27 ) demonstrated a significant increase in operative time, intraoperative blood loss and hospital stay with increasing weight of removed fibroid.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, OvaWatch test should not be used to evaluate adnexal mass suspicious for adnexal torsion. Surgical diagnosis is required for adnexal torsion and appropriate surgical management is recommended ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%